Evaluation of structural, optical and mechanical behaviour of L-argininium bis(trifluoroacetate) single crystal: an efficient organic material for second harmonic generation applications - Sonia, Ms (2019)
In the present technologically advanced era, non-linear optical materials especially organic derivatives are in the limelight due to their fast response in electro-optic switches and high nonlinear efficiency. Therefore, with respect to this behaviour, single crystals of L-argininium Bis(trifluoroacetate) (here in after called LABTF) an organic material was grown by slow evaporation solution growth technique. The grown single crystal was subjected to single crystal X-Ray diffractometer to validate its chemical structure and compound formation. The titled compound crystallizes into an asymmetric entity that comprises of one divalent L-argininium cation and two monovalent trifluoroacetic anion. All the intermolecular hydrogen bonds present in the LABTF crystal structure are investigated by 3D molecular Hirshfeld surface analysis and their relative involvements are disintegrated using 2D fingerprint plots. Further, the crystalline perfection assessment was performed using high-resolution X-Ray diffractometer which divulges the absence of structural grain boundaries in the obtained crystal. Thermal transport parameters of the titled compound were measured through Photoacoustic spectroscopy. The shock strength above which the crystal induces damage was found by the shock damage threshold technique. In addition, mechanical property related parameters such as hardness, stiffness and Young's Modulus were evaluated using the nanoindentation technique. These mechanical parameters resolve the reliability of devices and it can be enhanced by improving the crystal quality.